Reductive Upgrading of Biomass-Based Levulinic Acid to γ-Valerolactone Over Ru-Based Single-Atom Catalysts - Meng, Ye; Jian, Yumei; Chen, Dandan; Huang, Jinshu; Zhang, Heng; Li, Hu (Frontiers in Chemistry, 2022)
With the great adjustment of world industrialization and the continuous improvement of energy consumption requirements, the selective conversion of biomass-based platform molecules to high-value chemicals and biofuels has become one of the most important topics of current research. Catalysis is an essential approach to achieve energy-chemical conversion through the “bond breaking-bond formation” principle, which opens a broad world for the energy sector. Single-atom catalysts (SACs) are a new frontier in the field of catalysis in recent years, and exciting achievements have been made in biomass energy chemistry. This mini-review focuses on catalytic conversion of biomass-based levulinic acid (LA) to γ-valerolactone (GVL) over SACs. The current challenges and future development directions of SACs-mediated catalytic upgrading of biomass-based LA to produce value-added GVL, and the preparation and characterization of SACs are analyzed and summarized, aiming to provide theoretical guidance for further development of this emerging field.